STEM Education in Primary Schools: Mapping Global Trends and Uncovering Future Research Directions - Umar, Anggun Ravena; Regina Caeli, Gema Amades; Maulidah, Ismahyanti; Tresnawati, Nailah; Tarmidzi, Tarmidzi (Publikasi Pendidikan, 2025)
Although STEM education holds great promise for developing essential competencies among young learners, its implementation at the primary school level faces persistent structural and pedagogical barriers. These include limited alignment between curriculum design and children's cognitive development, insufficient teacher training and instructional resources, and unequal access to quality STEM programs, particularly in underserved regions. This study provides a comprehensive bibliometric overview of STEM education research in primary schools by analyzing 203 Scopus-indexed publications using RStudio. Through descriptive interpretation, the findings reveal a continuous upward trend in scholarly interest, reflecting the expanding adoption of STEM frameworks in elementary education. The analysis highlights that the progression of STEM literacy among primary school students is closely shaped by curriculum reform, teacher readiness, and equitable access to educational technologies. To maximize the relevance and societal impact of future research, the study recommends adopting an integrative and cross-disciplinary approach—one that emphasizes pedagogical transformation and curriculum innovation, in addition to technological advancement, to better prepare students for the demands of 21st-century learning.